A classificação de Robson: Apenas uma forma de classificar cesarianas? - Clode,Nuno (2017)
The Robson Ten-Group Classification System has been viewed by the majority of the clinicians as way of classifying cesarean section according to maternal characteristics. Recent WHO and FIGO statements suggest that Robson classification should be used by all healthcare facilities where deliveries occur to collect and analyze perinatal data